Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan KEelengkapan Imunisasi Tetanus Toksoid (TT) Di Puskesmas Lokbaintan Tahun 2013 - Akhmad Mahyuni, S.Sos., MPH; H. M. Noor S.Sos., MPH; Fathia Yunidai; STIKES Husada Borneo; Dinas Kesehatan Kabupaten Tanah Laut; Alumni STIKES Husada Borneo (HB PRESS, 2015)
Tetanus toxoid immunization to prevent tetanus useful for women of childbearing age and pregnant women. Tetanus cases found in tropical countries and countries that still have low health condition. WHO data shows, deaths from tetanus in developing countries 135 times higher than advanced countries. This study aimed to determine the relationship between knowledge and attitudes of pregnant women with tetanus toxoid immunization completeness in Public Health Center of Lokbaintan in 2013. Type a descriptive analytic study. The design of this study used a cross-sectional approach. Population in this research that all pregnant women with gestational age of three semester (28-37 weeks) in Public Health Center of Lokbaintan in 2013, amounting to 206 pregnant women. Samples were taken using random sampling techniques were 58 subjects. The result showed that the majority of respondents have sufficient knowledge of the 25 (43.1%), the majority of respondents have a positive attitude that is 38 (65.5%), most respondents did not complete the immunization of 37 (63.8%) and complete the 21 (36.2%). No association with complete knowledge of tetanus toxoid immunization Pregnant women (p = 0.164 > α = 0,05).The higher level of knowledge of the propensity of pregnant women pregnant women to do the higher tetanus toxoid immunization. No association with the attitude of tetanus toxoid immunization completeness Pregnant women (p = 0.062 > α = 0,05). The more positive attitude held pregnant women pregnant women the tendency to do the higher tetanus toxoid immunization. More mothers are expected to find the right information about the tetanus toxoid, the benefits, side effects, the impact of not getting immunized when tetanus toxoid and so forth. Mother in order to get immunity during pregnancy and protected from infection during childbirth for both mother and baby will be born.